JUDICIAL ACTIVISM IN BRAZIL: THE DILEMMA BETWEEN THE SEPARATION OF POWERS AND THE IMPLEMENTATION OF FUNDAMENTAL RIGHTS - Voltarelli Santos, Leonardo; Roberto Costa, Marcos; Alberto Martinelli, Marcos (Revista Gênero e Interdisciplinaridade, 2025)
This research addresses the issue of judicial activism in Brazil in light of the principle of separation of powers, focusing on the implementation of fundamental rights and analyzing whether this practice by the Judiciary constitutes a violation of said principle. The study explores the principle of separation of powers, its origin, purpose and contemporary application, as well as the system of checks and balances. In addition, it seeks to understand the interpretation and application of the legal norm, together with the limits of the creation of law by the judge. The study analyzes the phenomenon of judicial activism in Brazil, its history, concept, characteristics, causes, doctrinal criticisms, favorable positions, relevant cases and the activist action of the Supreme Federal Court.